PENGARUH PEMBERIAN TERAPI ANTIHIPERTENSI DAN PENURUN TEKANAN INTRAKRANIAL TERHADAP HARAPAN HIDUP PASIEN STROKE PERDARAHAN INTRASEREBRAL SELAMA MENJALANI RAWAT INAP DI RUMAH SAKIT UMUM PUSAT DR. SARDJITO YOGYAKARTA - , Luh Putu Febryana Larasanty, Prof. Dr. Zullies Ikawati, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Intracerebral hemorrhage (ICH) stroke is a type of stroke with the highest mortality rate, with only about 38% of patients who survived for the first year after stroke. Antihypertensive treatment and therapy for increased intracranial pressure is still the main therapy for reduce the mortality rate in ICH. The objective for this research is to study the effect of early antihypertensive treatment and therapy for increased intracranial pressure on life expectancy of patient with ICH stroke during hospitalization in Dr. Sardjito Hospital. One hundred and sixty five patients with ICH stroke who meet the inclusion and exclusion criteria divided into 2 major groups for cases control study. There were 81 patients in cases groups and 84 patients in control groups. Data collection conducted retrospectively through patient medical record. There were 8 (9,88%) patients in cases group and 19 (22,63%) patients in control group which didnât get early antihypertensive therapy. Furosemide, nimodipine and valsartan is the most commonly used antihypertensive for ICH patients during hospitalization. Patients which didnât get therapy for increased intracranial pressure as much as 35 (43,21%) patient in cases group and 36 (42,86%) patient in control group. Mannitol is one and the only agent used to treat increased intracranial pressure for ICH patient during hospitalization. Odds ratio for early antihypertensive therapy is 2,67 (95% Confidence Interval 1,09 â 6,50